Pelatihan Guru SMP Tentang Media Pembelajaran Matematika dan IPA Berbasis ICT Pada Kurikulum Merdeka Belajar - Yoel Octobe Purba; Sudirman T.P. Lumbangaol (CV Putra Publisher, 2023)
This community service activity aims to improve the competency of junior high school mathematics teachers at UPTD SMP Negeri 1 Jorlanghataran in making ICT-based mathematics learning media that are in accordance with the independent learning curriculum. Making ICT-based mathematics learning media is an alternative that teachers must have to increase their competence. On the other hand, this activity can improve teacher skills in writing teaching materials using instructional media. The method used in this community service activity is a collaborative-participatory dialogic approach including socialization and in-house training (lectures, questions and answers, discussions) for delivering material, hands-on practice for making learning media. To ensure the sustainability of training results and to receive support in improving the quality of learning, participants were given the task of making learning media outside of training hours. The training participants in the community service program activities totaled 50 participants. The participants stated that this activity was very useful and a new experience. This community service activity could run smoothly, well and even for the next activity they asked to be included again.